2014
DOI: 10.1007/s00213-014-3642-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher sensitivity to the conditioned rewarding effects of cocaine and MDMA in High-Novelty-Seekers mice exposed to a cocaine binge during adolescence

Abstract: Cocaine binge administration during adolescence induces a higher sensitivity to the rewarding effects of MDMA and cocaine in HNS mice in adulthood. This may explain the greater vulnerability often seen among individuals exposed early in life to drugs of abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…A recent study has shown that the novelty-seeking phenotype does not significantly correlate with either acquisition or drugseeking parameters of MDMA self-administration in rats [40]. However, following cocaine treatment, we have observed that an increase in the conditioned rewarding effects of MDMA is observed only in HNS mice, while no differences are observed in mice exposed to ethanol during adolescence [38,39]. Moreover, the numerous methodological differences make these studies very difficult to compare.…”
Section: Conditioned Place Preference Induced By Cocaine and Mdmamentioning
confidence: 62%
See 4 more Smart Citations
“…A recent study has shown that the novelty-seeking phenotype does not significantly correlate with either acquisition or drugseeking parameters of MDMA self-administration in rats [40]. However, following cocaine treatment, we have observed that an increase in the conditioned rewarding effects of MDMA is observed only in HNS mice, while no differences are observed in mice exposed to ethanol during adolescence [38,39]. Moreover, the numerous methodological differences make these studies very difficult to compare.…”
Section: Conditioned Place Preference Induced By Cocaine and Mdmamentioning
confidence: 62%
“…Head-dipping in the hole-board test has been proposed as a useful measure with which to examine the relationship between novelty-seeking and drug abuse [53]. Previous studies show that the hole-board test is more effective in identifying adolescent mice that will be sensitive to the conditioned rewarding effects of cocaine on the long-lasting effects of ethanol or cocaine [37][38][39]. The median was used in order to classify the mice as HNS versus LNS, as this is a standard measure when a set of data has been arranged in order of magnitude and is less affected by outliers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations